Taxation policy and gender employment in the Middle East and North Africa Region: A comparative analysis of Algeria, Egypt, Morocco, and Tunisia - Fofana, Ismaël; Corong, Erwin; Chatti, Rim; Bouazouni, Omar (International Food Policy Research Institute, 2012)
Empirical evidence suggests that women are more vulnerable to chronic poverty and gender inequality is likely to condition the impacts of policies on the rest of the economy and consequently on poverty itself. While gender-responsive budgeting has made significant headway into economic policy, taxation has lagged behind. Because tax policy is the most economically direct way by which governments can influence individual behavior, requests have been made for gender-responsive tax policy that promote gender equality. This study applied to Algeria, Egypt, Morocco, and Tunisia aims to contribute to this debate by assessing the induced gender employment bias of current taxation policies in these countries. It explores the pattern of male and female employment and discusses the indirect tax distortions across sectors within each country and between countries. The possible impact of the indirect tax distortion on male and female employment is quantitatively assessed using a gender-focused computable general equilibrium model. The analysis reveals that indirect taxes, in particular import duties, are biased for female employment in Algeria and Egypt, but not in Morocco and Tunisia. Female labor–intensive industries in Algeria and Egypt are highly protected in the benchmark and are not competitive internationally so that removing protection would increase competition with cheaper import substitutes and cause the sector to contract and lay off workers. In contrast, the same female labor–intensive industries are less protected in Morocco and Tunisia. Hence, removal of indirect taxes in these countries would result in quasi-neutral effects between male and female salary and wage earnings. The taxation policies in the Middle East and North Africa region have changed over the last decade and may undergo significant changes in the coming years. In light of this unpredictability, an assessment of the tax-related relative price bias on men and women constitutes a crucial step toward providing adequate guidance to planners, policymakers, and other stakeholders.